The Music Elements of Henan Traditional Guzheng Music - Zhao, Bo; Wongkhamchan, Kritsada; Kotchapakdee, Pat (Asian Journal of Traditional and Innovative Arts and Textiles, 2024)
This research is qualitative research with the objective of studying the music elements of Henan traditional Guzheng（古筝) music under the guidance of "Ethnomusicology" theory and "Cultural Ecology" theory. The data is collected from the target group of people related to Henan traditional Guzheng music, selected using the purposive sampling method. The collected data was analyzed according to the objectives through two types of data analysis: the analysis of the documents analysis of documents and field data. The formation of the Henan Guzheng music genre is a process that has undergone long-term accumulation. Centered around the Nanyang region, Henan Guzheng music is widely disseminated throughout the province, with this region also possessing rich cultural and historical materials related to Guzheng music research. Centered around the Nanyang region, Henan Guzheng music is widely disseminated throughout the province, with this region also possessing rich cultural and historical materials related to Guzheng music research. This study aims to explore the musical elements of Henan Guzheng music, revealing its formation and artistic background, including four aspects: music source, dialect tone, composition and playing techniques. Among these elements, the "Bantou-tune" and "Paizi-tune" within the "Dadiao-tune" serve as the main sources of traditional repertoire in the Henan Guzheng genre. The local style of Henan Guzheng music is rooted in the Henan dialect, with the technique of left-hand portamento effectively emulating vocalization on the Guzheng. Additionally, the musical style of Henan Guzheng music reflects the optimistic, simple, hearty, and straightforward characteristics of the people of Henan, with unique playing techniques distinct from other genres. These musical elements collectively shape the distinctive local characteristics of Henan Guzheng music expression. This research can enable people in diverse music cultures to learn more about the Henan Guzheng genre and the cultural connotations behind it.